2010
DOI: 10.1213/ane.0b013e3181cdb06b
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol and Landiolol, Selective β1-Adrenoreceptor Antagonists, Provide Neuroprotection Against Spinal Cord Ischemia and Reperfusion in Rats

Abstract: These data show that ultrashort-acting selective beta(1)-adrenoreceptor antagonists can reduce neurological injury in a rat model of spinal cord ischemia-reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…In previous studies, it has been found that esmolol shows antioxidant properties by reducing lipid peroxidation markers [13]. Esmolol has been found to reduce histological and motor disorders caused by spinal cord I/R damage and has protective effect against spinal cord I/R injury [14]. At the same time, protective efficacy has been determined in transient ischemic attacks [8].…”
Section: Lower-limb Ischemia-reperfusionmentioning
confidence: 99%
“…In previous studies, it has been found that esmolol shows antioxidant properties by reducing lipid peroxidation markers [13]. Esmolol has been found to reduce histological and motor disorders caused by spinal cord I/R damage and has protective effect against spinal cord I/R injury [14]. At the same time, protective efficacy has been determined in transient ischemic attacks [8].…”
Section: Lower-limb Ischemia-reperfusionmentioning
confidence: 99%
“…The liver and kidneys were dissected totally and fixed in buffered formalin for 7 days. The experimental model was carried out according to the experimental studies in the literature that investigate the spinal cord and visceral organ damage after cross-clamping the aorta [17][18][19][20].…”
Section: Tissue Preparationmentioning
confidence: 99%
“…To assess the degree of ischemic neuronal injury, the number of normal motor neurons in the anterior horn of the spinal cord (anterior to a line drawn through the central canal perpendicular to the vertebral axis) was counted in 3 sections for each animal and averaged. 24 Terminal deoxynucleotidyl transferase (TdT)-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) staining was performed following the protocol provided by the manufacturer (S7100, Millipore). Spinal cord sections were deparaffinized, rehydrated, digested with 20 mg/ml proteinase K (Sigma Chemical) for 30 minutes at room temperature, quenched with 3% hydrogen peroxide for 5 minutes at room temperature, rinsed in phosphate-buffered saline (PBS), and subsequently incubated with a reaction solution composed of 55 ml/5 cm 2 of working strength TdT enzyme under a humidified atmosphere for 60 minutes at 37°C.…”
Section: Histopathological Evaluationmentioning
confidence: 99%